Caffeine inhibition of aflatoxin synthesis: probable site of action. - Buchanan, R L (1984)
Aflatoxin production by pregrown cultures of Aspergillus parasiticus was completely inhibited by incorporation of 2 mg of caffeine per ml into the medium. This was accompanied by a decrease in glucose utilization and an inhibition of oxygen uptake and carbon dioxide evolution. Enzyme analyses indicated no significant differences in specific activities on glucose-6-phosphate dehydrogenase, mannitol dehydrogenase, phosphofructokinase, fructose 1,6-diphosphatase, pyruvate kinase, or malate dehydrogenase. Glucose uptake kinetics indicated a linear dose-related inhibition of glucose uptake. It appears likely that caffeine inhibits aflatoxin synthesis by restricting the uptake of carbohydrates which are ultimately used by the mold to synthesize this family of mycotoxins.